Response of Mungbean (cvs. Celera II-AU and Jade-AU) and Blackgram (cv. Onyx-AU) to Transient Waterlogging - Kyu, Khin Lay; Malik, Al Imran; Colmer, Timothy David; Siddique, Kadambot H. M.; Erskine, William (Frontiers in Plant Science, 2021)
Mungbean (Vigna radiata (L.) Wilczek) and blackgram (Vigna mungo (L.) Hepper) are important crops for smallholder farmers in tropical and subtropical regions. Production of both crops is affected by unexpected and increasingly frequent extreme precipitation events, which result in transient soil waterlogging. This study aimed to compare the waterlogging tolerance of mungbean and blackgram genotypes under varying duration of waterlogging stress at germination and at seedling stages. We evaluated the responses to different durations of transient waterlogging in a sandy clay loam under temperature-controlled glasshouse conditions. Waterlogging durations were 0, 1, 2, 3, 4, 5, 6, 7, 8 days during germination and 0, 2, 4, 8, 16 days during the seedling stage. We used two mungbean genotypes (green testa), Celera II-AU (small seeded) and Jade-AU (large seeded), contrasting in seed size and hypocotyl pigmentation, and a blackgram genotype (black testa), Onyx-AU. Waterlogging reduced soil redox potential, delayed or even prevented germination, decreased seedling establishment and affected shoot and root development. In the seedlings waterlogged at 15 days after sowing, adventitious root formation and crown nodulation varied between the genotypes and 16 days of waterlogging substantially reduced growth but did not result in plant death. Plants in soil with waterlogging for 8–16 days followed by drainage and sampling at 39 days after sowing had reduced shoot and root dry mass by 60–65% in mungbean and 40% in blackgram compared with continuously drained controls, due at least in part to fewer lateral roots. SPAD chlorophyll content was also reduced. Blackgram Onyx-AU was more tolerant to transient waterlogging than the two mungbeans in both growth stages. Of the two mungbean genotypes, Celera II-AU had greater seedling establishment than Jade-AU post waterlogging imposed at sowing. In contrast, Jade-AU had more plant biomass and greater recovery growth than Celera II-AU after waterlogging and recovery during the seedling stage. Both species were delayed in emergence in response to the shorter periods of transient waterlogging at germination, and with the longer waterlogging germination and emergence failed, whereas at the seedling stage both showed adaptation by the formation of adventitious roots.